Sustainable Design of Eco-Friendly Skyscraper for the Modern Society - Vinima Gambhir, Dr; Ram Kumar; Sreyansu Satya Prakash; V. Pushparajesh, Dr; Daljeet Pal Singh; Ankit Punia; Manish Nagpal (Architecture Image Studies Scientific Journal)
The industrial revolution and technological advancement started in the 18th century have a lot to boast for its success in many aspects of human life like reduction in infant mortality rate, human life expectancy, education, health, global food production etc. But the development and gains have many flip sides also. It is not sustainable in long run. It is undermining the ability of the environment and ecosystem, disturbing the fine balance of nature on the planet which is threatening the lives of many species on earth. The main cause of Environmental problems is excessive emission of Green House Gases (GHG) like CO2, NO2, SO2, CO etc. due to the burning of fossil fuels to meet the energy demand of human beings and reduction in forest cover. This project proposes the design of a sustainable and eco-friendly skyscraper that incorporates cutting-edge green technologies and innovative design strategies to minimize its environmental footprint. The design aims to reduce energy consumption by 50% through renewable energy sources, harvest and reuse rainwater and greywater to reduce water consumption by 75%, and incorporate green spaces and vertical gardens to improve air quality. The study reveals that the presence of the green building Movement is far better in the South and Western part and lesser in the Northern and further lesser in the Eastern part of the country. It is an indicator of adaptability and awareness in the regions. The adoption of the Green Building Concept is significantly influenced by economic growth, the existence of international and multinational corporations, and incentives from regional urban authorities.